2018
DOI: 10.1177/2050640618761702
|View full text |Cite
|
Sign up to set email alerts
|

Metal versus plastic stents for drainage of pancreatic fluid collection: A meta‐analysis

Abstract: Metal stents are superior to plastic stents for endoscopic transmural drainage of PFC because they have a higher clinical success rate and lower rate of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 38 publications
(123 reference statements)
0
44
0
2
Order By: Relevance
“…In the recent years, the debate regarding the appropriate stent for EUS‐guided PFC drainage has again come into the spotlight. Several systematic reviews with traditional pairwise meta‐analysis comparing metal and plastic stents in EUS‐guided PFC drainage are available . Although these data showed that metal stents improved clinical outcomes and safety compared with plastic stents, some important questions remained unaddressed, such as which metal stent improves clinical outcomes and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, the debate regarding the appropriate stent for EUS‐guided PFC drainage has again come into the spotlight. Several systematic reviews with traditional pairwise meta‐analysis comparing metal and plastic stents in EUS‐guided PFC drainage are available . Although these data showed that metal stents improved clinical outcomes and safety compared with plastic stents, some important questions remained unaddressed, such as which metal stent improves clinical outcomes and safety profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the treatment cost (LCMS: US$12155 vs. plastic stents: US$6609) and stent related adverse events were higher in the LCMS group (32.3 vs. 6.9%, p = 0.01) [24]. Several systematic reviews and meta-analyses draw conflicting conclusions while comparing plastic stents vs. metal stents for ETD of PFCs [32][33][34][35][36][37]. In three of the published systematic reviews and meta-analyses, metal stents were found superior to plastic stents for both pseudocysts as well as WON in terms of clinical success and adverse events [34,36,32].…”
Section: Endoscopic Transmural Drainage: Choice Of Stentsmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses draw conflicting conclusions while comparing plastic stents vs. metal stents for ETD of PFCs [32][33][34][35][36][37]. In three of the published systematic reviews and meta-analyses, metal stents were found superior to plastic stents for both pseudocysts as well as WON in terms of clinical success and adverse events [34,36,32]. On the contrary, two other systematic reviews and meta-analyses did not find a difference in the outcomes between metal or plastic stents [33,37].…”
Section: Endoscopic Transmural Drainage: Choice Of Stentsmentioning
confidence: 99%
“…Another development in the stent evolution, lumen apposing metal stent (LAMS) development where this stent is used not only for endoscopic drainage procedure, but also for endoscopic necrosectomy procedure. This stent has also advantage in migration prevention when compared to FCMS [32][33][34][35].…”
Section: Endoscopic Management: Metal Vs Plastic Stentmentioning
confidence: 99%